Global‐scale characterization of turning points in arid and semi‐arid ecosystem functioning. Issue 7 (7th April 2020) - Bernardino, Paulo N.; De Keersmaecker, Wanda; Fensholt, Rasmus; Verbesselt, Jan; Somers, Ben; Horion, Stéphanie
Abstract: Aim: Changes in dryland ecosystem functioning are threatening the well‐being of human populations worldwide, and land degradation, exacerbated by climate change, contributes to biodiversity loss and puts pressures on sustainable livelihoods. Here, abrupt changes in ecosystem functioning [so‐called turning points (TPs)] were detected using time series of Earth observation data. Hotspot areas of high TP occurrence were identified, observed changes characterized and insights gained on potential drivers for these changes. Location: Arid and semi‐arid regions. Time period: 1982–2015. Methods: We used a time series segmentation technique (breaks for additive season and trend) to detect breakpoints in rain‐use efficiency as a means of analysing changes in ecosystem functioning. A new typology to characterize the detected changes was proposed and evaluated, at regional to local scales, for a set of case studies. Ancillary data on population and drought were used to provide insights on potential drivers of TP occurrence. Results: Turning points in ecosystem functioning were found in 13.6% ( c . 2.1 × 10 6  km 2 ) of global drylands. Turning point hotspots were primarily observed in North America, the Sahel, Central Asia and Australia. In North America, the majority of TPs (62.6%) were characterized by a decreasing trend in ecosystem functioning, whereas for the other regions, a positive reversal in ecosystem functioning was prevalent. Further analysis showed that: (a) both climatic and anthropogenic pressure influenced the occurrence of TPs in North America; (b) Sahelian grasslands were primarily characterized by drought‐induced TPs; and (c) high anthropogenic pressure coincided with the occurrence of TPs in Asia and Australia. Main conclusions: By developing a new typology targeting the categorization of abrupt and gradual changes in ecosystem functioning, we detected and characterized TPs in global drylands. This TP characterization is a first crucial step towards understanding the drivers of change and supporting better decision‐making for ecosystem conservation and management in drylands.